2001
DOI: 10.1177/000992280104000904
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Screening of Children Diagnosed with Congenital Heart Defects

Abstract: Children with congenital heart disease (CHD) are more likely than normal children to have developmental delays. The development of 64 children with CHD less than 6 years old was screened with the Denver II. Thirty-five of the 64 children had CHD that required surgical or catheter intervention. These 35 children were significantly less likely than other children with CHD to be normal on developmental screening (46% vs 86%, respectively). Thirty-four percent of children with more severe CHD were referred for ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
1
20
1
Order By: Relevance
“…The need for routine developmental follow-up evaluation for this population has been suggested previously [6, 17, 24, 30, 37], but most pediatric cardiac centers do not routinely assess these patients for developmental delay as part of standard clinical care [20]. More recently, pediatric cardiac programs have developed ND follow-up programs to meet the needs of this group of patients [5].…”
Section: Discussionmentioning
confidence: 99%
“…The need for routine developmental follow-up evaluation for this population has been suggested previously [6, 17, 24, 30, 37], but most pediatric cardiac centers do not routinely assess these patients for developmental delay as part of standard clinical care [20]. More recently, pediatric cardiac programs have developed ND follow-up programs to meet the needs of this group of patients [5].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Children with CHD have been found to have higher rates of attention problems, behavioral problems, visual-motor/visual-spatial defi-cits, fine and gross motor delays, and language difficulties when compared to the normal population. 19,[27][28][29][30] Parents of children with CHD may view their children as "normal" in spite of developmental delays, 31 and thus, may not seek out early intervention services, even if they are recommended. 19,[27][28][29][30] Parents of children with CHD may view their children as "normal" in spite of developmental delays, 31 and thus, may not seek out early intervention services, even if they are recommended.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26] It has been suggested that these children would benefit from routine developmental followup. 19,[27][28][29][30] Parents of children with CHD may view their children as "normal" in spite of developmental delays, 31 and thus, may not seek out early intervention services, even if they are recommended. Furthermore, the availability of services through early intervention programs has declined over the years due to budget cuts, 32 and there is a growing concern that without a routine developmental follow-up program, many children with CHD in need of services may not be identified.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] More recently, research has suggested that patients requiring cardiac surgery early in life would benefit from routine developmental followup. 8,12,13 In 2012, a comprehensive scientific statement was published by the American Heart Association (AHA) and later endorsed by the American Academy of Pediatrics providing an algorithm for evaluating and managing patients with CHD who are at risk for developmental delay. 14 Cardiac surgical centers have developed specialized developmental follow-up programs for children with CHD, yet it is unknown if these specialized programs will have a clinical impact.…”
Section: Introductionmentioning
confidence: 99%